2016
DOI: 10.1073/pnas.1609291113
|View full text |Cite
|
Sign up to set email alerts
|

Reducing C-terminal truncation mitigates synucleinopathy and neurodegeneration in a transgenic model of multiple system atrophy

Abstract: Multiple system atrophy (MSA) is a sporadic orphan neurodegenerative disorder. No treatment is currently available to slow down the aggressive neurodegenerative process, and patients die within a few years after disease onset. The cytopathological hallmark of MSA is the accumulation of alpha-synuclein (α-syn) aggregates in affected oligodendrocytes. Several studies point to α-syn oligomerization and aggregation as a mediator of neurotoxicity in synucleinopathies including MSA. C-terminal truncation by the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
87
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 65 publications
4
87
0
Order By: Relevance
“…PLP‐hαSyn mice also develop progressive SND characterized by a 30% reduction in the number of dopaminergic neurons (tyrosine hydroxylase positive [TH + ] neurons) in the SNc compared to healthy control animals. This neuronal loss is already present at 4 months of age and is followed by a significant reduction in density of dopaminergic terminals and in number of medium spiny neurons in the striatum at 12 months of age . SN and striatum are both essential for motor control, and the loss of neurons in these two brain areas leads to motor impairment in these mice …”
mentioning
confidence: 99%
“…PLP‐hαSyn mice also develop progressive SND characterized by a 30% reduction in the number of dopaminergic neurons (tyrosine hydroxylase positive [TH + ] neurons) in the SNc compared to healthy control animals. This neuronal loss is already present at 4 months of age and is followed by a significant reduction in density of dopaminergic terminals and in number of medium spiny neurons in the striatum at 12 months of age . SN and striatum are both essential for motor control, and the loss of neurons in these two brain areas leads to motor impairment in these mice …”
mentioning
confidence: 99%
“…Therefore, a caspase‐1 inhibitor could exert neuroprotective effects on synucleinopathies by reducing αSyn cleavage, hence limiting its toxicity and its ability to form aggregates. An in vivo proof of concept of the ability of a caspase‐1 inhibitor to mitigate αSyn pathology and to mediate neuroprotection in a pathologic and phenotypic transgenic mouse model of MSA, the PLP‐SYN mice, was conducted and showed that such caspase‐1 inhibition prevented motor deficits in PLP‐SYN mice compared with placebo controls . More importantly, caspase‐1 inhibition was able to limit the progressive toxicity of αSyn aggregation by reducing its load in the striatum of PLP‐SYN mice .…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo proof of concept of the ability of a caspase‐1 inhibitor to mitigate αSyn pathology and to mediate neuroprotection in a pathologic and phenotypic transgenic mouse model of MSA, the PLP‐SYN mice, was conducted and showed that such caspase‐1 inhibition prevented motor deficits in PLP‐SYN mice compared with placebo controls . More importantly, caspase‐1 inhibition was able to limit the progressive toxicity of αSyn aggregation by reducing its load in the striatum of PLP‐SYN mice . Not only did caspase‐1 inhibition reduce truncated αSyn but also decreased its monomeric and oligomeric forms .…”
Section: Discussionmentioning
confidence: 99%
“…Here, the companion paper by Bassil et al (2) furthers our understanding of how caspase-1-mediated truncation, oligomerization, and aggregation of αSyn in glia may mediate neurotoxicity in vivo. Bassil et al (2) studied PLP-SYN tg mice, in which the promoter of the myelin-associated proteolipid protein (PLP) drives αSyn overexpression in oligodendrocytes and thereby models key aspects of MSA, including GCIs, neuroinflammation, dopaminergic cell loss, and motor deficits (22).…”
mentioning
confidence: 89%
“…Scientists have begun identifying factors that may initiate or accelerate αSyn aggregation and how this process relates to progressive impairment of neuronal structure and function. In PNAS, companion papers by Wang et al (1) and Bassil et al (2) establish a compelling link between the accumulation of C-terminally truncated forms of αSyn created by caspase-1 and cellular dysfunction in culture and in vivo, all potentially initiated by inflammatory insults.…”
mentioning
confidence: 99%